Peptides from plants and microorganisms: a defense strategy for biotic and abiotic stresses - Ha-Tran, Dung Minh; Huang, Chieh-Chen (Frontiers in Plant Science, 2025)
Antimicrobial peptides (AMPs) from plants and microorganisms have emerged as promising tools due to their multifunctional roles in plant defense. These small, bioactive molecules, such as thionins, systemins, defensins, cyclotides, hevein-like peptides, and cyclic dipeptides, exhibit broad-spectrum activity against fungal pathogens, bacteria, and insect pests. Recent studies have further elucidated their supportive roles in conferring tolerance to abiotic stresses, including salinity, drought, and heavy metals exposure, thus expanding their potential applications. Previous studies demonstrated that the integration of AMPs genes into transgenic crops has shown significant potential in improving plant resistance to both biotic and abiotic stresses. Importantly, in our recent study, a cyclic dipeptide cyclo(L-Ala-Gly) from Priestia megaterium BP01R2 enables salinity stress alleviation in plants. The latest finding revealed that cyclo(His-Pro) in Arabidopsis navigated carbon flux from glycolysis to the pentose phosphate pathway and its supplementation increased NADPH levels and the NADPH/NADP+ ratio in plants. This review explores the latest advances in the application of plant- and microorganisms-derived AMPs, with a focus on their functional mechanisms and their roles in the development of stress-resilient crops. It also provides an overview of ongoing efforts to harness peptides in sustainable agricultural practices.